The Antifungal Activity of Naphthoquinones: An Integrative Review - FUTURO, DÉBORA O.; FERREIRA, PATRICIA G.; NICOLETTI, CAROLINE D.; BORBA-SANTOS, LUANA P.; SILVA, FERNANDO C. DA; ROZENTAL, SONIA; FERREIRA, VITOR FRANCISCO (Anais da Academia Brasileira de Ciências, 2018)
Naphthoquinones are the most commonly occurring type of quinones in nature. They are a diverse family of secondary metabolites that occur naturally in plants, lichens and various microorganisms. This subgroup is constantly being expanded through the discovery of new natural products and by the synthesis of new compounds via innovative techniques. Interest in quinones and the search for new biological activities within the members of this class have intensified in recent years, as evidenced by the evaluation of the potential antimicrobial activities of quinones. Among fungi of medical interest, yeasts of the genus Candida are of extreme importance due to their high frequency of colonization and infection in humans. The objective of this review is to describe the development of naphthoquinones as antifungals for the treatment of Candida species and to note the most promising compounds. By using certain criteria for selection of publications, 68 reports involving both synthetic and natural naphthoquinones are discussed. The activities of a large number of substances were evaluated against Candida albicans as well as against 7 other species of the genus Candida. The results discussed in this review allowed the identification of 30 naphthoquinones with higher antifungal activities than those of the currently used drugs.